2009
DOI: 10.1007/s11069-009-9442-8
|View full text |Cite
|
Sign up to set email alerts
|

A real-time operation optimization model for flood management in river-reservoir systems

Abstract: In this paper, a new methodology has been developed for real-time flood management in river-reservoir systems. This methodology is based upon combining a Genetic Algorithm (GA) reservoir operation optimization model for a cascade of two reservoirs, a hydraulic-based flood routing simulation model in downstream river system, a Geographical Information System (GIS) based database, and application of K-Nearest Neighbor (K-NN) algorithm for development of optimal operating rules. The GA optimization model estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…In flood damage estimation model, peak flow frequency analysis was conducted. Flood damages were estimated by linking a hydraulic flood routing model with GIS tools for considering land-use information and flood damage functions in the downstream floodplain of the reservoir (Malekmohammadi et al 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In flood damage estimation model, peak flow frequency analysis was conducted. Flood damages were estimated by linking a hydraulic flood routing model with GIS tools for considering land-use information and flood damage functions in the downstream floodplain of the reservoir (Malekmohammadi et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Applications of metaheuristic techniques to flood problems are described in several studies (Chang and Chen 1998; Karaboga et al 2004;Ngo et al 2007;Kumar et al 2010;Malekmohammadi et al 2010). However, one particularly promising metaheuristic technique, the harmony search (HS) algorithm, described below, has not yet been tested or applied to flood models.…”
mentioning
confidence: 99%
“…Chang et al (2010) reported a real-time reservoir operation mode for flood control using artificial intelligent techniques. Malekmohammadi et al (2010) developed a real-time flood management model for riverreservoir systems based upon combining a reservoir operation based upon a genetic algorithm with a hydraulic flood routing simulation for routing reservoir releases in the downstream river. The operation model determines the hourly releases that minimize the flood damages in the downstream river.…”
Section: Previous Optimization/simulation Modelsmentioning
confidence: 99%
“…To scale the inputs and the targets, the normalized equation, Equation (6), is often used, forcing the data to fall within a specified range.…”
Section: Back Propagation Neural Network (Bpnn)mentioning
confidence: 99%